The Benefits of Joining a Multidisciplinary Research Team - Mailloux, Logan O.; Grimaila, Michael R.; Hodson, Douglas D.; Baumgartner, Gerald B. (IEEE potentials, 2017)
Exciting research challenges often present themselves as complex problems-they are inherently difficult to understand and require multiple domains of expertise to solve. As a result, teamwork is becoming the everyday norm in most professional settings and is often required when studying topical problems (e.g., autonomous vehicles, cyberphysical, renewable energy, among others). For students, learning to operate within, and eventually lead, a team is a necessary and valuable skill that will benefit them throughout their professional lives.